Improving the Quality of Students of SD Negeri 2 Rantau Pulut Lifestyle Characterized by Clean Water and Renewable Energy: Peningkatan Kualitas Gaya Hidup Siswa SD Negeri 2 Rantau Pulut Bercirikan Air Bersih dan Energi Terbarukan - Fatiqin, Awalul; Alfanaar, Rokiy; Rahman, Sudarman; Febrianto, Yahya; Riana, Shesanti Citra; Karyadi, Karyadi; Sahari, Yudhi Ekakristian; Gunawan, Yohanes Edy; Arsana, Mu'afa Purwa; Suprayogi, Thathit (NAWASENA : JOURNAL OF COMMUNITY SERVICE, 2023)
Clean water is a vital requirement for children at the primary school level as it supports their learning process. The availability of clean water not only facilitates learning activities but is also an important aspect in supporting a lifestyle that is responsible for natural resources, especially in the context of using renewable energy. The emphasis on an appropriate lifestyle in the utilisation of clean water became the focus of the community service conducted at SD Negeri 2 Rantau Pulut. Through this socialisation activity, students were given an understanding of the importance of a clean lifestyle that utilises clean water sources wisely, while integrating the use of renewable energy. The results of this service showed positive progress. Students' understanding of the importance of a clean lifestyle and the utilisation of clean water with renewable energy has increased significantly, reaching an understanding level of 91.67%. From this, it can be concluded that this socialisation successfully achieved its goal of raising students' awareness of the importance of clean water and a sustainable lifestyle.